Shared decision-making about colorectal cancer screening: A conceptual framework to guide research - Christy, Shannon M. (2013)
OBJECTIVE: To develop a conceptual framework to guide research on shared decision-making about colorectal cancer (CRC) screening among persons at average risk and their providers. METHODS: Based upon a comprehensive review of empirical literature and relevant theories, a conceptual framework was developed that incorporated patient characteristics, cultural beliefs, provider/health care system, health beliefs/stage of adoption, and shared decision-making between patients and providers that may predict behavior. Relationships among concepts in the framework, shared decision-making process and outcomes, and CRC screening behavior were proposed. Directions for future research were presented. RESULTS: Many of the concepts in the proposed framework have been examined in prior research. However, these elements have not been combined previously to explain shared decision-making about CRC screening. CONCLUSION: Research is needed to test the proposed relationships and hypotheses and to refine the framework. PRACTICE IMPLICATIONS: Findings from future research guided by the proposed framework may inform clinical practice to facilitate shared decision-making about CRC screening.